A comparative analysis of aesthetic preferences in Chinese freehand paintings among Chinese retired elders beyond gender - Abd Shukor, Shureen Faris; Wu, Jiamei; Hasna, Mohd Fabian; Daud, Mohd Najmi (Springer Nature, 2025)
Using the nominal group technique (NGT) and a structured questionnaire, this study investigates whether gender differences influence preferences for various attributes of Chinese freehand painting, a traditional Chinese painting technique, among retired Chinese individuals. First, the NGT was used to identify 17 attributes desired by the population. These attributes were then used to formulate the questionnaire, which allowed for the identification and prioritization of key characteristics through group discussion. The questionnaire was completed by 116 male and 117 female participants, enabling a comparative analysis of preferences between genders. The findings indicate that gender does not significantly affect preferences for most attributes of Chinese freehand painting. Specific characteristics, such as “the colour should not be too bright;” “relaxed, simple, and flexible brushwork;” and “natural scenery,” showed no significant gender-based differences, suggesting a shared appreciation among male and female participants. Although minor variations were observed for certain attributes, these differences were not substantial enough to suggest that gender is a primary factor in shaping aesthetic preferences. This study concludes that retirees’ preferences regarding Chinese freehand painting are not significantly influenced by gender. This study provides new insights into the art preferences of retired individuals, supporting the development of marketing strategies and art education programmes for older populations. By exploring retirees’ perceptions of Chinese freehand painting, this study contributes to the promotion and cultural inheritance of this traditional art form. The findings highlight consistent patterns of appreciation across genders rather than significant gender-based differences.